A dinucleotide motif in oligonucleotides shows potent immunomodulatory activity and overrides species-specific recognition observed with CpG motif - Kandimalla, Ekambar R. (National Academy of Sciences, 2003)
Bacterial and synthetic DNAs containing CpG dinucleotides in specific sequence contexts activate the vertebrate immune system through Toll-like receptor 9 (TLR9). In the present study, we used a synthetic nucleoside with a bicyclic heterobase [1-(2′-deoxy-β-d-ribofuranosyl)-2-oxo-7-deaza-8-methyl-purine; R] to replace the C in CpG, resulting in an RpG dinucleotide. The RpG dinucleotide was incorporated in mouse- and human-specific motifs in oligodeoxynucleotides (oligos) and 3′-3-linked oligos, referred to as immunomers. Oligos containing the RpG motif induced cytokine secretion in mouse spleen-cell cultures. Immunomers containing RpG dinucleotides showed activity in transfected-HEK293 cells stably expressing mouse TLR9, suggesting direct involvement of TLR9 in the recognition of RpG motif. In J774 macrophages, RpG motifs activated NF-κB and mitogen-activated protein kinase pathways. Immunomers containing the RpG dinucleotide induced high levels of IL-12 and IFN-γ, but lower IL-6 in time- and concentration-dependent fashion in mouse spleen-cell cultures costimulated with IL-2. Importantly, immunomers containing GTRGTT and GARGTT motifs were recognized to a similar extent by both mouse and human immune systems. Additionally, both mouse- and human-specific RpG immunomers potently stimulated proliferation of peripheral blood mononuclear cells obtained from diverse vertebrate species, including monkey, pig, horse, sheep, goat, rat, and chicken. An immunomer containing GTRGTT motif prevented conalbumin-induced and ragweed allergen-induced allergic inflammation in mice. We show that a synthetic bicyclic nucleotide is recognized in the C position of a CpG dinucleotide by immune cells from diverse vertebrate species without bias for flanking sequences, suggesting a divergent nucleotide motif recognition pattern of TLR9.